Chemical and morphological effects of the contraceptive hormone 17 α-ethynylestradiol on fluid lipid membranes - Ruiz, Gilia Cristine Marques [UNESP]; do Carmo Morato, Luis Fernando [UNESP]; Pazin, Wallance Moreira [UNESP]; Milano, Francesco; Constantino, Carlos José Leopoldo [UNESP]; Valli, Ludovico; Giotta, Livia (My University, 2021)
The lack of studies involving the effects in human health associated with the chronic ingestion of pollutants lead to the path of investigating the action of these compounds in cell membrane models. We demonstrated the interaction (causes and consequences) of the hormone 17 α-ethinylestradiol (EE2) with lipid monolayers (prepared as Langmuir films) and bilayers prepared as small unilamellar vesicles (SUVs) and giant unilamellar vesicles (GUVs). Both fluidity and majority chemical composition of real plasma cell membrane were guaranteed using the phospholipid 1-palmitoil-2-oleoyl-sn-glycero-3-phosphatidylcholine (POPC). Surface pressure-mean molecular area (π-A) isotherms and PM-IRRAS measurements highlighted the strong interaction of EE2 with POPC monolayers, leading the hormone to remain at the air/water interface and promoting its penetration into the phospholipid hydrophobic chains. In the case of bilayers, the entrance of the hormone inside the SUV is likely facilitated by their high curvature. In GUVs, EE2 was responsible for changes in the spherical shape, forming structures like buds and lipid protrusions. The set of results indicates the strong effects of EE2 on fluid membranes, which is an important feature to predict its damage in human cells.
Keywords: 17α-ethynylestradiol; Giant unilamellar vesicles; Langmuir monolayers; PM-IRRAS; POPC; Small unilamellar vesicles